Analysis of effectiveness of monetary policy transmission in the dual monetary system in Indonesia / Taufiq Chaidir and Akhyani Wulandini - Chaidir, Taufiq; Wulandini, Akhyani (2019)
Bank Indonesia (BI) as the monetary authority, was given a new responsibility, namely to carry out a dual monetary policy (MP) namely conventional and sharia MP. In relation to the current transmission mechanism of monetary policy (TMMP), the pattern of sharia MP transmission taken by BI is similar to conventional. Therefore, BI is required to provide uniformity of policy signals within the MP framework. Thus, the pattern of sharia MP transmission can use the same pattern and channel as conventional MP transmission (Solikin, et al. 2018). MP framework covers the implementation and strategy of MP. The framework is generally related to achieving the ultimate goal of price stability, economic growth, and expansion of employment opportunities, and strategies to achieve them (exchange rate targeting, monetary targeting, inflation targeting, implicit but not explicit anchor) (Warjiyo, 2004). TMMP works require time (time lag). The time lag of each channel can be different from the others. The exchange rate channel usually works faster because the impact of changes in interest rates to exchange rates works very fast. The conditions of the financial and banking sectors also have a significant influence on MP transmission speed. MP effectiveness is the extent to which MP taken by the central bank (whatever its form) has a positive impact on the economy and society, in the sense that it can increase economic growth; can improve people's welfare; can increase employment opportunities; can increase state foreign exchange earnings; and give influence to other macro policies. MP effectiveness is measured by two indicators, namely how much speed or deadline (time lag) and how the strength of the variables in each channel responds to the changes (shock) monetary policy instruments (rSBIS) and other variables until the realization of the MP goal. (Natsir, 2008). The Noviasri study (2012) revealed that in controlling Islamic MP inflation more effective than conventional.